Cover Picture: Controlled Tetradeuteration of Straight‐Chain Fatty Acids: Synthesis, Application, and Insight into the Metabolism of Oxidized Linoleic Acid (Angew. Chem. Int. Ed. 25/2022). Issue 25 (24th May 2022) - Watanabe, Ayako; Hama, Kotaro; Watanabe, Kohei; Fujiwara, Yuko; Yokoyama, Kazuaki; Murata, Shigeo; Takita, Ryo
Abstract : The light of deuterium shines in the darkness of the molecular mechanism of the oxidized phosphatidylcholine synthesis. A concise protocol for the controlled tetradeuteration of straight‐chain fatty acids is reported by Kotaro Hama, Ryo Takita, and co‐workers (e202202779 ). The use of four deuterium atoms in fatty acids as well as a diagnostic peak of phosphatidylcholines thus obtained enabled the identification of acyltransferases that transfer the acyl moiety derived from an oxidized linoleic acid.